Consanguinity and family clustering of male factor infertility in Lebanon - Inhorn, Marcia C; Kobeissi, Loulou; Nassar, Zaher; Lakkis, Da'ad; Fakih, Michael H (Fertility and sterility, 2009)
To investigate the influence of consanguineous marriage on male factor infertility in Lebanon, where rates of consanguineous marriage remain high (29.6% among Muslims, 16.5% among Christians). Clinic-based, case-control study, using reproductive history, risk factor interview, and laboratory-based semen analysis. Two IVF clinics in Beirut, Lebanon, during an 8-month period (January-August 2003). One hundred twenty infertile male patients and 100 fertile male controls, distinguished by semen analysis and reproductive history. None. Standard clinical semen analysis. The rates of consanguineous marriage were relatively high among the study sample. Patients (46%) were more likely than controls (37%) to report first-degree (parental) and second-degree (grandparental) consanguinity. The study demonstrated a clear pattern of family clustering of male factor infertility, with patients significantly more likely than controls to report infertility among close male relatives (odds ratio = 2.58). Men with azoospermia and severe oligospermia showed high rates of both consanguinity (50%) and family clustering (41%). Consanguineous marriage is a socially supported institution throughout the Muslim world, yet its relationship to infertility is poorly understood. This study demonstrated a significant association between consanguinity and family clustering of male factor infertility cases, suggesting a strong genetic component.